2014
DOI: 10.1038/ismej.2014.221
|View full text |Cite
|
Sign up to set email alerts
|

Life-cycle modification in open oceans accounts for genome variability in a cosmopolitan phytoplankton

Abstract: Emiliania huxleyi is the most abundant calcifying plankton in modern oceans with substantial intraspecific genome variability and a biphasic life cycle involving sexual alternation between calcified 2N and flagellated 1N cells. We show that high genome content variability in Emiliania relates to erosion of 1N-specific genes and loss of the ability to form flagellated cells. Analysis of 185 E. huxleyi strains isolated from world oceans suggests that loss of flagella occurred independently in lineages inhabiting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
78
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(79 citation statements)
references
References 58 publications
1
78
0
Order By: Relevance
“…Amphimedon queenslandica ). The presence of only three fragmented dynein genes in Emiliania huxleyi was attributed to the loss of most flagellar genes in the sequenced strain and is not a characteristic of the species itself (von Dassow et al 2015). Thus, given the deep taxonomic sampling of this study, loosing a single axonemal dynein is a rare event.…”
Section: Resultsmentioning
confidence: 99%
“…Amphimedon queenslandica ). The presence of only three fragmented dynein genes in Emiliania huxleyi was attributed to the loss of most flagellar genes in the sequenced strain and is not a characteristic of the species itself (von Dassow et al 2015). Thus, given the deep taxonomic sampling of this study, loosing a single axonemal dynein is a rare event.…”
Section: Resultsmentioning
confidence: 99%
“…Remarkably, diploid-haploid switching is triggered by sensing specific E. huxleyi viruses (EhVs) that infect and destroy diploid, but not haploid cells (61). However, genomic evidence suggests that putative asexual lineages of E. huxleyi that lost the ability to switch to the haploid stage have recurrently emerged in populations inhabiting oligotrophic open oceans, perhaps as a consequence of low levels of EhVs in these environments (62).…”
Section: Sex In Eukaryotic Microorganisms: More Voyeurs Neededmentioning
confidence: 99%
“…But the exact cause of differential survival between coastal and oceanic taxa is still not known. Further, von Dassow et al () showed that coastal, highly productive, and seasonally cycling parts were populated with Emiliania huxleyi strains maintaining the biphasic life‐cycle, while a loss of flagella and 1N phase occurred in some open ocean sub‐populations of E. huxleyi . von Dassow et al () speculate that this loss of the haploid phase could be related to lower biotic pressure and low environmental variability of the ocean, as opposed to highly variable environmental conditions of neritic environments that favor sexuality (von Dassow et al ).…”
mentioning
confidence: 99%